Thermodynamic and structural variations along the olivenite–libethenite solid solution - J. Majzlan; A. Plumhoff; M. Števko; M. Števko; G. Steciuk; J. Plášil; E. Dachs; A. Benisek (European Journal of Mineralogy, 2023)
Many natural secondary arsenates contain a small fraction of phosphate. In this work, we investigated the olivenite–libethenite (Cu2(AsO4)(OH)–Cu2(PO4)(OH)) solid solution as a model system for the P–As substitution in secondary minerals. The synthetic samples spanned the entire range from pure olivenite (Xlib=0) to libethenite (Xlib=1). Acid-solution calorimetry determined that the excess enthalpies are non-ideal, with a maximum at Xlib=0.6 of +1.6 kJ mol−1. This asymmetry can be described by the Redlich–Kister equation of Hex= Xoli⋅Xlib [A+B(Xoli−Xlib)], with A=6.27 ± 0.16 and B=2.9 ± 0.5 kJ mol−1. Three-dimensional electron diffraction analysis on the intermediate member with Xlib=0.5 showed that there is no P–As ordering, meaning that the configurational entropy (Sconf) can be calculated as -R(Xoliln⁡Xoli+Xlibln⁡Xlib<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="117pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="52aa0657e629b45c533e40c23cb7d950"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-35-157-2023-ie00001.svg" width="117pt" height="13pt" src="ejm-35-157-2023-ie00001.png"/></svg:svg>). The excess vibrational entropies (<msubsup>Svibex</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="19pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="4f3877a6f78dba53722e4db12cf389ef"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-35-157-2023-ie00002.svg" width="19pt" height="15pt" src="ejm-35-157-2023-ie00002.png"/></svg:svg>), determined by relaxation calorimetry, are small and negative. The entropies of mixing (Sconf+<msubsup>Svibex</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="53pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="81532243ab3fb035e24c018f95ce5a01"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-35-157-2023-ie00003.svg" width="53pt" height="15pt" src="ejm-35-157-2023-ie00003.png"/></svg:svg>) also show asymmetry, with a maximum near Xlib=0.6. Autocorrelation analysis of infrared spectra suggests local heterogeneity that arises from strain relaxation around cations with different sizes (As5+ /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6ab83fe49e60fc98c8f39a665eb0d5b9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-35-157-2023-ie00004.svg" width="8pt" height="14pt" src="ejm-35-157-2023-ie00004.png"/></svg:svg> P5+) in the intermediate members and explains the positive enthalpies of mixing. The length scale of this strain is around 5 Å, limited to the vicinity of the tetrahedra in the structure. At longer length scales (≈15 Å), the strain is partially compensated by the monoclinic–orthorhombic transformation. The volume of mixing shows complex behavior, determined by P–As substitution and symmetry change. A small (0.9 kJ mol−1) drop in enthalpies of mixing in the region of Xlib=0.7–0.8 confirms the change from monoclinic to orthorhombic symmetry.